Income Analysis of Local Rabbit Fattening (Lepus nigricollis) Basal Fed with Carrot Leaf (Daucus Carota L.) Waste and Concentrate Supplementation - E. K., Dewi; Putri, B. R. T.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The aim of this study are to observe the level of farming income in fattening local rabbits which were given a basic feed of carrot leaf waste which was supplemented with concentrates in different levels. This study uses a Randomized Block Design (RBD). Twenty male rabbits aged 7 weeks were divided into four treatments. The treatment of concentrate level  0g (R0 / control), 15g (R1), 30G (R2), and 45g (R3), each consisting of five rabbits used individual cages measuring 70cm x 50cm x 50cm. Forage feed in the form of carrot leaves is given ad libitum. The data used is primary data and secondary data. Management is explained descriptively based on observations. While the analysis of level income in fattening local rabbit is seen based on cost analysis, income analysis, R / C ratio analysis and BEP. The results showed that the largest total revenue was treatment of R3 Rp. 397,350.5 - with a total cost of Rp. 333,823. Based on cash costs, the highest total income is in treatment R0, which is Rp 113,631.9 with an R/C ratio of 1.47 while the revenue is treatment with the addition of concentrate is lower at Rp 83,301.6 (R1); Rp.69,658.1 (R2) and Rp.66,526.5 (R3) as well as an R/C ratio of 1.30 (R1); 1.24 (R2) and 1.19 (R3). BEP unit and BEP prices for each treatment are 2 head (R0); and 3 head  (R1); (R2); (R3) with a price of Rp. 48,043.6 (R0); Rp. 54,819.7 (R1); Rp. 58,888.4 (R2) and Rp. 66,764.7 (R3). It was concluded that the addition of concentrate was still less profitable compared to carrot leaf-based maintenance without the addition of concentrates. Keyword: consentrate supplementation, carrot leaves, income analysis, rabbits